THE LEGAL SUPPORT OF ORGANIZATIONAL AND ECONOMIC PROCESSES OF MUNICIPAL WASTE MANAGEMENT IN THE EUROPEAN UNION AND UKRAINE - Д.Т.Д. Ель-Рабай’а; В.М. Марченко (Економіка та право)
The article clarifies the substantial organizational and economic risks ahead, on the way for Ukraine to meet its committed targets to transform waste management system to become in full accordance with those implemented in the European Union. Both, European and Ukrainian legislation in this regard are analyzed, categorized, and compared to highlight the core differences and identify the gaps in the ones that are implemented in Ukraine. The environmental and economic results of waste management in Germany and Ukraine revealed, that Ukraine is not demonstrating satisfactory improvement during the last 7 years since the association agreement was signed. The article identifies 5 key recommendations, that would allow Ukraine to match up with European countries in municipal waste management (household waste management according to Ukrainian classification system), these recommendation are summarized as follows: centralized legislation approach, where all essential regulations are approved by the central government and unified for all regions; promptness, and operative attitude to take all necessary actions related to waste management; guaranteeing measurability and control over each waste management stage, that should lead to creating fully informative digital database; implementing “Peeling away method” to ensure that all potential secondary raw material and high calorific value waste is reused of converted into alternative energy resources; and finally, creating comprehensive and cohesive legislative package that works all together as integrated system. Centralized/local legislative distribution analysis, and structure of public information on waste in the official portal are provided for the first time in a scientific research, to the best knowledge of the authors. “The peeling away method”, described in this article, is used for the first time as well, to explain in simple way, the European strategy to minimize the amount of waste that is sent to landfill.